Alloyed Palladium–Silver Nanowires Enabling Ultrastable Carbon Dioxide Reduction to Formate. Issue 4 (4th December 2020) - Han, Na; Sun, Mingzi; Zhou, Yuan; Xu, Jie; Cheng, Chen; Zhou, Rui; Zhang, Liang; Luo, Jun; Huang, Bolong; Li, Yanguang
Abstract: Palladium can enable the electrochemical CO2 reduction to formate with nearly zero overpotential and good selectivity. However, it usually has very limited stability owing to CO poisoning from the side reaction intermediate. Herein, it is demonstrated that alloying palladium with silver is a viable strategy to significantly enhance the electrocatalytic stability. Palladium–silver alloy nanowires are prepared in aqueous solution with tunable chemical compositions, large aspect ratio, and roughened surfaces. Thanks to the unique synergy between palladium and silver, these nanowires exhibit outstanding electrocatalytic performances for selective formate production. Most remarkably, impressive long‐term stability is measured even at < ‐0.4 V versus reversible hydrogen electrode where people previously believed that formate cannot be stably formed on palladium. Such stability results from the enhanced CO tolerance and selective stabilization of key reaction intermediates on alloy nanowires as supported by detailed electrochemical characterizations and theoretical computations. Abstract : Alloyed Pd–Ag nanowires exhibit significantly improved stability for electrochemical CO2 reduction to formate at potentials where it was previously believed that the product could not be stably formed on Pd. This is due to the markedly enhanced CO tolerance and selective stabilization of key reaction intermediates on alloy nanowires.